(untitled) (Jurnal Bahasa, 2001)
This article reports the findings of an exploratory study on the communicative competence of secondary school Malay essays. The main purpose of the study was to identify the communicative components in essays (performance) i.e. an anthentic form to evaluate the communicative competence. The study applied Hyme’s communicative idea to evaluate writing proficiency through a communicative and a discourse model. Research data were gathered from three types of essay namely explanatory, persuasive, and expressive. Factor analysis was used to analyze the data. The study showed the presence of grammar, discourse and, sociolinguistics components in all the three types of essay. Each component is made up of a number of subcomponents which are the modification of the communicative model used. Grammar was the principle components for all types of essay. Jn explanatory and persuasive essays the arrangement of variants are; grammar; discourse and; sociolinguistics. As for expressive essay the arrangement is grammar; sociolinguistics and; discourse.